Genetic evaluation of sperm abnormality traits in Holstein Friesian crossbred bulls using random regression models - AMBIKE, VRINDA B; R, VENKATARAMANAN; KARTHICKEYAN, S M K; TIRUMURUGAAN, K G; BHAVE, KAUSTUBH G; KHADSE, JAYANT (The Indian Journal of Animal Sciences, 2023)
Genetic parameters of sperm abnormality traits were evaluated in HF crossbred bulls using Bayesian univariate, bivariate and random regression models. Data from 161 bulls on 1,527 ejaculates collected from 2010 to 2020 at BAIF (Bharatiya Agro Industries Foundation) was utilized for this study. Four sperm abnormality traits viz. total abnormalities (A), head abnormality (HA), mid-piece abnormality (MA) and tail abnormality (TA) were included in the analysis. Gibbs sampling was done to implement a Bayesian framework. Means for A, HA, MA and TA were 10.77%, 2.99%. 2.61% and 5.10% respectively. Heritability and repeatability estimates obtained from univariate analysis were below 0.1. Genetic correlations obtained for the total abnormalities with semen production traits like ejaculate volume, sperm concentration, initial sperm motility, post-thaw motility and the total number of spermatozoa were negative. Heritability and repeatability estimates were higher in the case of random regression models where the values tend to increase with the age of the bulls. Heritability ranged from 0.025 (3 years) to 0.139 (10 years) for total abnormality estimates. In general, the estimates of genetic parameters for abnormality were low and found to increase with age.